Решите уравнение:2х(х+3) в квадрате - 3х(х-1)(х+8)= х в квадрате ( -х-9)+21
Решите уравнение:
2х(х+3) в квадрате - 3х(х-1)(х+8)= х в квадрате ( -х-9)+21
Ответ(ы) на вопрос:
Гость
[latex]2x(x+3)^2- 3x(x-1)(x+8)= x^2( -x-9)+21 \\\ 2x(x^2+6x+9)-3x(x^2+7x-8)=-x^3-9x^2+21 \\\ 2x^3+12x^2+18x-3x^3-21x^2+24x=-x^3-9x^2+21 \\\ 42x=21 \\\ x= \frac{21}{42} =0.5[/latex]
Ответ: 0,5
Гость
2x^3 +12x^2+ 18x -(3x^3+24x^2-3x^2-24x)=-x^3-9x^2+21
2x^3+12x^2+18x-3x^3-24x^2+3x^2+24x+x^3+9x^2-21 =0
42x - 21 =0
42[ = 21
x =0,5
Не нашли ответ?
Похожие вопросы